Frequency Effect on Embankment Under Soft Soil Using Seismic Loading - Ripon Hore; Mehedi Ahmed Ansary (Scientific Trends, 2022)
The main objective of the research is to model the wrap faced embankment on the soft clay foundation by applying shake table test. To investigate the dynamic behaviour like acceleration amplification, displacement and pore water pressure of the wrap faced embankment with respect to different frequency changed (1 Hz,2 Hz, 3 Hz, 5 Hz, 8 Hz 10 Hz, 12 Hz and 15 Hz), fixed acceleration (0.05g) and surcharge (1.71 kPa) were used laminar box on shake table testing machine . The laminar box placed on the shake table machine, lab test for preparing reconstitute soil sample and wrap faced embankment with frequency arrangement are the main elements of this research. After applying all test parameters, dynamic parameters increased with increasing the elevation with respect to frequency. These models have also been was also verified experimented by numerical analysis by using PLAXIS 3D. The output results from both the experiments and numerical analyses have showed that the maximum dynamic parameters were found at the 10 Hz of the test. The errors in the numerical analyses with respect to experimental results was are less than 5%. This output results are very helpful to understand the relative performances of the wrap faced embankment which is accelerating the update design parameters.
Keywords: Clayey Soil, Frequency, Wrap Faced, Shake Table Test